Macedonia and Its Population (Czech Journal of International Relations, 2002)
Hugh Poulton: Who are the Macedonians? C. Hurst & Co. /Publishers/ Ltd., 38 King Street, London WC2E 8JT, 2nd edition, revised 2000, 218 stran, ISBN 1-85065-534-0.